THE RELATIONSHIP BETWEEN CHEWING FOOD AND SLEEPING DISORDERS CAUSED BY DENTAL AND ORAL DISEASES TO PRESCHOOL CHILDREN’S FOOD INTAKE - Ristya Widi Endah Yani (Media Kesehatan Masyarakat Indonesia, 2016)
Food intake is a directly influential factor in determining nutritional status of preschool children. Dental and oral diseases generally cause pain in teeth which make them have difficulty to eat and sleep well. This situation can result in reduced food intake. The research objective was to analyze the relationship between chewing food and sleeping disorders caused by dental and oral diseases to preschool children’s food intake. An analytic observational study with cross sectional design in preschool age children was conducted in District Ambulu, Jember Regency. A hundred and two samples were taken using purposive sampling method. The variables studied were chewing food and sleeping disorders considering oral diseases (using ecohis index) and food intake (using 24-hour recall). The data were analyzed using Spearman correlation test. The result showed that there is a negative correlation between the variables of chewing food and sleeping disorders in consequence of oral diseases to food intake. The more severe chewing food and sleep disorders caused by oral diseases, the lower the food intake of preschool children.